CYBERSPACE ANALYSIS IN NA'VI AVATAR FILM AS A REQUIREMENT OF VIRTUAL SPACES - AFRINA, CUT (LPPM Institut Seni Indonesia Padangpanjang, 2021)
Cyberspace as Virtual space embodiment in Na'vi's Avatar Film by using the analysis theory according to Mark Slouka. The purpose of the Film Avatar analysis is to further understand the elements of the Cyberspace in the film, the results of the analysis of the authors on the movie Avatar is the advancement of technology and communication with a network capable of creating Cyberspace in a life. Where the human sense of being now leads to machine culture as a product of media communication technology is Internet. Cyberspace in the movie Aavatar is able to disrupt the balance that is on the Na'vi community. Cyberspace's identity built in the Avatar is a modern human-controlled indetity. Technology is the human work that is controlled by human beings themselves. The results of the Avatar technology product are not solely acceptable to the Na'vi community. The integrity and solidarity of the Na'vi community to defend the earth of Pandora, with a teeter fight against the sophistication of modern human technology.